PyAutoTk: bridging usability and flexibility in web automation frameworks - OLIVEIRA, Gabriel Ramos Rodrigues (2025)
The accelerating adoption of agile methodologies, DevOps practices, and digital transformation has increased the demand for faster, more efficient, and higher-quality deliverables across various industries [Rajkumar et al. 2016]. Automation has become essential not only for software development and QA teams but also for professionals in marketing, sales, and operations seeking to streamline repetitive tasks [Ahmed et al. 2010]. However, existing tools often present significant challenges in terms of learning curve, initial setup, and accessibility, especially for users with limited technical background [Ijaz and Andlib 2014]. PYAUTOTK emerges as a Python-based automation framework focused on lowering the learning curve and simplifying the creation of automated scripts. By aligning the concept of widgets with fundamental HTML and CSS principles, it reinforces understanding of how elements work and interact. The framework also integrates with the Page Object Model (POM) architecture, supporting both beginners and QA professionals starting in automation. Its modular design, flexibility, and usability-focused approach address common challenges in test automation. Preliminary validation suggests that PYAUTOTK offers benefits in terms of usability and maintainability, although further empirical studies are necessary to confirm these results. Current limitations include OS compatibility, lack of Playwright support, and limited advanced action features—prioritized for future development.